1999
DOI: 10.1128/mcb.19.8.5373
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role in DNA Metabolism for the Binding of Fen1/Rad27 to PCNA and Implications for Genetic Risk

Abstract: Fen1/Rad27 nuclease activity, which is important in DNA metabolism, is stimulated by proliferating cell nuclear antigen (PCNA) in vitro. The in vivo role of the PCNA interaction was investigated in the yeast Rad27. A nuclease-defective rad27 mutation had a dominant-negative effect that was suppressed by a mutation in the PCNA binding site, thereby demonstrating the importance of the Rad27-PCNA interaction. The PCNA-binding defect alone had little effect on mutation, recombination, and the methyl methanesulfona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
124
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(131 citation statements)
references
References 55 publications
7
124
0
Order By: Relevance
“…For instance, Resnick and colleagues (25,26) have used a FEN1 mutant that harbors a D to A substitution at a residue found to be critical for DNA processing to determine the in vivo substrates of the flap endonuclease. Using either genetically engineered yeast strains or exogenously expressing yeast systems, they show that the FEN1 mutant causes genetic instability and increased sensitivity to MMS, likely by preventing processing of DNA replication intermediates and promoting the formation of recombinogenic DNA double-strand breaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Resnick and colleagues (25,26) have used a FEN1 mutant that harbors a D to A substitution at a residue found to be critical for DNA processing to determine the in vivo substrates of the flap endonuclease. Using either genetically engineered yeast strains or exogenously expressing yeast systems, they show that the FEN1 mutant causes genetic instability and increased sensitivity to MMS, likely by preventing processing of DNA replication intermediates and promoting the formation of recombinogenic DNA double-strand breaks.…”
Section: Discussionmentioning
confidence: 99%
“…For example, such a mutation in the flap endonuclease, FEN1 (i.e., a D to A substitution), resulted in a dominant-negative form of the human and yeast protein that bound substrate DNAwith high affinity and blocked subsequent nucleic acid processing in vivo (25,26). Prior studies have established the importance of the acidic residues E96 and D210 to the enzymatic repair activity of APE1 ( Fig.…”
Section: Ap Endonuclease and Dna Binding Properties Of The Ed Proteinmentioning
confidence: 99%
“…Since protein-protein interactions can modulate the enzyme activities, e.g. PCNA can enhance the processivity of DNA polymerase ␦ and FEN1 activity (35,72,73), experiments to study the effects of APE, PCNA, and RPA on hMYH glycosylase activity are underway. …”
Section: Discussionmentioning
confidence: 99%
“…The amounts of Fen1 were 0.1 ng (2.4 fmol), 1 ng (24 fmol), and 10 ng (240 fmol), respectively. C, depletion of the assay reveals that Fen1 activity is dependent on the presence of both PCNA and RF-C. data using yeast strains with mutations within this conserved region (21,30). In another report, it was suggested that the basic C-terminal tail of Fen1 was also important for the interaction with PCNA, because a deletion mutant lacking 17 amino acids at the C terminus failed to interact with PCNA, although this mutant still contained an intact PCNA interaction motif (17).…”
Section: Discussionmentioning
confidence: 99%